Companion teacher based on sociological stimulus during learning to improves the acceptance of inclusive education pupils in receiving skills and information - Husin, Mohd Razimi; Shaffeei, Kama; Ahmad, Hishamuddin; Shuib, Tajul Rosli (Linguistics and Culture Review, 2021)
This study aims to reveal about the acceptance of pupils in the skills and information learn done by teachers with companion teachers during teaching and learning sessions (T&L) to inclusive learning disability (LD) pupils. This study also aims to understand the specific characteristics of the pupils’ learning styles based on their tendency to learn and the ability to process new information. This study is a case study using qualitative data to answer the questions stated. Researchers used the Dunn and Dunn Model as a guide in analyzing observational data of sociological stimuli in a learning style supported by video recordings, field notes, interviews, and analysis of student work outcomes. 6 participants were purposefully selected for this study among teachers, pupils, and parents. To identify individual learning style stimuli, observations on the behaviors exhibited by pupils along with the quality of learning and achievement outcomes recorded during the T&L process or after the T&L process. During the T&L process, characteristics or behaviors that reflect certain tendencies or elements of learning styles that exist in pupils will be assessed. Findings show that the stimulus of sociological learning style that is adjacent or next-to-pupils by teachers encourage or stimulate student learning.